(untitled) (Learning to Teach Language Arts, Mathematics, Science, and Social Studies Through Research and Practice, 2019)
Writing anxiety is an issue that affects students in all classes, but especially in writing-intensive courses like English language arts. Students with writing anxiety exhibit a range of behaviors, making it difficult for teachers to diagnose and prevent. Research has highlighted several possible solutions, but studies most consistently suggest improving students’ writing self-efficacy beliefs as a means of reducing writing anxiety. Several research-based strategies, such as using peer reviews and the process writing approach, are useful in improving self-efficacy beliefs. Teachers should research the best strategies to reduce anxiety in their students, but should ultimately encourage students to believe that they can succeed.